2020
DOI: 10.1002/ehf2.13082
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effects of longitudinal changes in left ventricular ejection fraction with cardiac resynchronization therapy

Abstract: Aims Left ventricular ejection fraction (LVEF) is considered an indicator of cardiac resynchronization therapy (CRT). Longitudinal studies on the predictive value of LVEF are scarce. We aimed to comprehensively evaluate the prognostic role of LVEF in the outcomes of Chinese patients with CRT. Methods and results Three hundred ninety-two patients were divided into three tertiles of LVEF: ≤25%, 25-30%, and 30-35%, and four groups by LVEF changes: <0% (negative response); ≥0% and ≤5% (non-response); >5% and ≤15% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our study identified five variables that independently correlated with HFiEF: younger age, smaller LVEDD, beta‐blocker use, AF ablation, and CRT implantation were positive predictors. The result was consistent with a few other studies: our subjects with HFiEF were more likely to be younger 6,9 and treated with a beta‐blocker 9 and CRT implantation 13 . Moreover, smaller LVEDD was an independent factor that predicted a greater likelihood of LVEF improvement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study identified five variables that independently correlated with HFiEF: younger age, smaller LVEDD, beta‐blocker use, AF ablation, and CRT implantation were positive predictors. The result was consistent with a few other studies: our subjects with HFiEF were more likely to be younger 6,9 and treated with a beta‐blocker 9 and CRT implantation 13 . Moreover, smaller LVEDD was an independent factor that predicted a greater likelihood of LVEF improvement.…”
Section: Discussionsupporting
confidence: 92%
“…The result was consistent with a few other studies: our subjects with HFiEF were more likely to be younger 6,9 and treated with a beta-blocker 9 and CRT implantation. 13 Moreover, smaller LVEDD was an independent factor that predicted a greater likelihood of LVEF improvement. Otherwise, the novel findings of this study are that patients with AF ablation had greater odds of being in the HFiEF group.…”
Section: Factors That Predict Heart Failure With Improved Ejection Fractionmentioning
confidence: 92%
“…The baseline patient characteristics are derived from the electronic medical record, including basic inpatient information, surgical records, and discharge summaries. The details of CRT implantation have been described in previous studies [ 9 ]. Demographic information (age, gender) was obtained by questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of CRT implantation has been described in detail previously. 17 The inclusion and exclusion criteria for the study are shown in detail in Table S1 . The Ethics Committee approved this study of Fuwai Hospital, Chinese Academy of Medical Sciences (IRB2012-BG-006).…”
Section: Methodsmentioning
confidence: 99%